Dyssynergia cerebellaris myoclonica (Ramsay Hunt syndrome): a condition unrelated to mitochondrial encephalomyopathies. Issue 2 (February 1989) - Tassinari, C A; Michelucci, R; Genton, P; Pellissier, J F; Roger, J
Abstract : Thirteen patients with dyssynergia cerebellaris myoclonica (Ramsay Hunt syndrome) had full clinical and neurophysiological study as well as muscle biopsy. The patients had action myoclonus, generalised epileptic seizures, and mild cerebellar syndrome. The disease was inherited in an autosomal recessive pattern in five patients, and occurred as isolated cases in the remaining eight patients. The age at onset of symptoms ranged from 6 to 15 years (mean, 10.4 years). The EEG and polygraphic findings included normal background activity in most patients, spontaneous fast generalised spike-and-wave discharges, photosensitivity, no activation during slow sleep, and vertex and rolandic spikes in REM sleep. Results of muscle biopsy, performed an average of 14 years after onset of the disease, were normal and showed no mitochondrial abnormalities. These findings suggest that Ramsay Hunt syndrome is a condition with distinctive clinical and neurophysiological features and unrelated to mitochondrial encephalomyopathies.